Digital Literacy Development Strategy in Higher Education Institutions - Jayadi, Agus; Ikawati, Hastuti Diah; Abdurrahman, Abdurrahman; Irawan, M. Ary (UNDIKMA, 2025)
This study aims to analyze the digital literacy development strategy in higher education institutions with a focus on three main aspects: (1) the digital literacy development strategy implemented, (2) the challenges faced in implementing the digital literacy program, and (3) the effectiveness of the program in improving students' ability to use technology critically and ethically. The research method used is a qualitative approach with a case study at a university in West Nusa Tenggara. Data were obtained through interviews with students, lecturers, and digital literacy program managers as well as analysis of relevant policy documents. The results of the study indicate that the strategies implemented include the integration of digital literacy into the curriculum, training for lecturers and students, and the development of technology infrastructure. However, the main challenges faced include limited infrastructure, lecturers' resistance to technology, and students' lack of critical and ethical understanding of using technology. The digital literacy program has proven effective in improving students' technical skills, but needs strengthening in the aspects of information evaluation and digital ethics. This study suggests the need for increased continuous training for lecturers, strengthening of technological infrastructure, and increasing student awareness of the importance of digital literacy holistically.